Reinforcement bar Corrosion - Causes and Management (2019)
Concretes are composite materials which decay as a result of steel corrosion in concrete structures is mostly accelerated in environments laden with chlorides and industrial effluent gases as well as harsh chemicals employed in and those generated from wastes in agricultural industries. This review summarises the effects of various environmental pollutants which promote deterioration of concretes with resultant corrosion of reinforcing bar (rebar). An overview of traditional and current methods for significant reduction of this mode of material deterioration is described. Discussions on management tools for rebar corrosion in agricultural and marine environments have been highlighted. Repair methods include the traditional application of patch repair mortar which has been modified with polymeric materials to improve adhesion and reduce porosity. The use of cathodic protection system to reduce rebar corrosion to its barest minimum has gained currency. Attention should be directed at corrosion reduction practices at the design and planning stages as well as modification concrete mixes with modified agricultural wastes/products and polymers.